(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Recent investigations into the human gut microbiome have substantially deepened our knowledge of microbial colonization, maturation, and dysbiosis across health and disease. The gut microbiota’s extensive metabolic repertoire and its central role in regulating host physiology make it an attractive target for novel therapeutics. Microbiome-based interventions seek to reshape the gut ecosystem via additive, subtractive, or modulatory approaches, employing native or engineered microbes, antibiotics, bacteriophages, and bacteriocins. These strategies present innovative alternatives to conventional treatments by enabling personalized, integrative, and potentially more sustainable care. Although the healthcare sector increasingly recognizes the therapeutic and economic promise of microbiome-based therapies, most candidates remain in early development and confront substantial technical, regulatory, and translational hurdles. This review surveys the current landscape of microbiome therapeutics, emphasizing clinical applications, development status, and future directions for integrating the microbiome into modern medicine.